Factors that Make it Easy to Overcome Obstacles to Curriculum Development in Vocational Institutions - Sobari, Mochamad; Rusman, Rusman; Shogbesan, Yusuf Olayinka (Universitas Negeri Semarang, 2024)
The curriculum must keep up with the times to meet the evolving needs of society. Responsive curriculum development poses challenging problems for curriculum designers in vocational education and other higher professions, although as such there is little study on this topic. This research focuses on how the process of developing a responsive curriculum for vocational education, and other higher professions based on the results of a literature review methods with data sources consisting of a collection twenty-six articles that are putated with process of gathering and arranging information or data from multiple sources is referred to as data collection identifying six supporting components of the responsive curriculum development process: (1) Vision of Education and Learning, (2) Continuous and iterative curriculum development process, (3) Collaboration, (4) involving all contributors, (5) The presence of favorable environmental factors and circumstances, and (6) Representatives of the institution. The importance of paying equal attention to each of these aspects is the main focus. By integrating these components, curriculum creators can design adaptable programs that are efficacious across the whole learning process. This strategy necessitates a shift in mentality and heightened exertion from all tiers of educational establishments, but ultimately results in a curriculum that is more comprehensive and adaptable.